'When East Meets West': Perception of and Responses to Stigma Among Ethnic Minority Students from Eastern Indonesia in Java - Muhiddin, Syurawasti; Zakiyah, Siti Nur Ainun; Sitorus, Mayrina Yanita; Liem, Andrian; Kiling, Indra Yohanes; Safrina, Elfydha Siti (Faculty of Psychology, Universitas Gadjah Mada, 2025)
Ethnic minorities and indigenous people are two of the many groups at high risk of being stigmatized in society because of their identity. Such stigmatization might have diverse psychological and social impacts. This study aimed to explore the perceptions of stigma experienced by ethnic minority students and their responses to it. This study was descriptive qualitative research involving 12 participants aged 18–30 from East Nusa Tenggara and Sulawesi, who had studied and lived in Yogyakarta for at least one year. Thematic analysis with an inductive approach resulted in three grand themes according to research questions: forms of stigma, coping strategies, and efforts to minimize stigma. Findings indicate that the stigma experienced by students was classified as stereotypes and negative treatment in both academic and non-academic contexts. Participants' responses to cope with the stigma were mainly related to four types of coping: problem-focused, emotion-focused, cognitive coping, and avoidance. There are three key areas of improvement that can reduce the occurrence of stigma in ethnic minority groups, namely self-development, relationship development, and institutional development (e.g., education and community). This research provides insights for key stakeholders, such as families, educational and youth institutions, and the media, to formulate interventions aimed at reducing stigma that may have negative psychosocial impacts on individuals and groups at both the individual and community levels.